Impact of under-filled k2edta coated blood collection tube on test results of complete blood count, reticulocyte count and white blood cell differential count - Karunanithi, Laavanya (Universiti Sains Malaysia, 2025)
High blood sample rejection rate is a prominent issue faced by hematology laboratories these days due to insufficient sample collection especially in pediatric, geriatric and oncology patients where venous access is difficult. Under-filled blood collection tubes affect the blood-to-anticoagulant ratio negatively leading to inaccurate results. This study evaluated the accuracy and reliability of complete blood count, reticulocyte count and white blood cell differential count parameters from under-filled blood collection tubes compared to standard volumes tubes. In this study, the aim is to compare hematological parameters across different collection volumes; 0.5 ml, 1.0 ml, 1.5 ml, and 2.0 ml in 2.0 ml standard lavender top K2EDTA tubes. The results have shown that most parameters remain consistent and were within clinically acceptable ranges in volumes as low as 1.5 ml. Some parameters, such as red blood cell (x1012/l), hematocrit (%) and lymphocyte (x109/l) remain stable even at 1.0 ml. This excludes hemoglobin, which has significant differences to all lower volumes. Therefore, under-filled tubes may be used as an alternative, reducing sample rejections and reducing overall healthcare costs. Future studies should include diverse populations and different analysers to support the findings